Polyethylene, compaction and chemical treatments to reduce the seepage losses from irrigation channels - Lima, Luiz Antonio (Pesquisa Agropecuaria Brasileira, 2014)
Efficiency and costs of polyethylene, compaction or chemical treatment to reduce the seepage loss from irrigation channels built in a Dark-Red Latosol of Cerrado soil were compared. Reductions in hydraulic conductivity of 102 soll samples treated with different concentrations of NaOH or Na2CO3 suggested respectively the application of 3 and 4 g/l to reduce seepage loss from irrigation channels. Application of 25 l/m2 of NaOH on the soil samples caused reductions greater than 95% in the hydraulic conductivity. In the channels the reduction was 73% when the channel was allowed to dry and 75% when the seepage tests were conducted just after the chemical treatment. Application of 25 l/m2 of Na2CO3 imparted a similar reduction (81%) when the seepage tests were conducted just after the chemical treatment. When the channel was allowed to dry, the reduction was only 48%. It is possible that this low reduction was due to the soil structure already being modified before the chemical treatment with Na2CO3. Due to the lack of expansive clays in this soil and the precipitation of aluminum by sodium containing compounds, it is believed that the reductions on seepage loss were caused by blockage of macropores with, particles displaced from aggregates disrupted by the removal of cementing agents. Among the alternatives compared, the polyethylene was the best, since it completely stopped the seepage loss from the irrigation channel. The compaction, which raised the bulk density from 1.03 to 1.52 g/cm3 reduced approximately 90% the seepage loss. Comparing the costs, the polyethylene was 15 times more expensive than chemical treatment and 5 times more expensive than soil compaction.
Keywords: soils; hydraulic conductivity; sodium